Reconstruction Scheme: Yes Bank Crisis Case - Malik, Rashika (IIUM Journal of Case Studies in Management, 2022)
It was 5 March 2020; Reserve Bank of India (RBI) superseded Yes Bank’s board of directors and placed it under a 30-day moratorium as the financial position of the bank was seriously being deteriorated. The withdrawal of cash by people having accounts in Yes bank was restricted at ?50000 By RBI under the terms of moratorium which created a panic among the customers of Yes Bank as well as the general public as this was leading to lack of their confidence in Indian banking system, but the involvement of RBI into the case was somewhere able to store their confidence back. To administer the case, Prashant Kumar who was deputy managing director and chief financial officer of State Bank of India (SBI) was appointed as an administrator at that time.